La città, il viaggio, il turismo: Percezione, produzione e trasformazione - Maria Ines Pascariello (FedOA - Federico II University Press, 2018)
The city as a destination of the journey in his long evolution throughout history: a basic human need, an event aimed at knowledge, to education, to business and trade, military and religious conquests, but also related to redundancies for the achievement of mere physical or spiritual salvation. In the frame of one of the world's most celebrated historical city, the cradle of Greek antiquity, myth and beauty, travel timeless destination for culture and leisure, and today, more than ever, strongly tending to the conservation and development of their own identity, this collection of essays aims to provide, in the tradition of AISU studies, a further opportunity for reflection and exchange between the various disciplines related to urban history.